PENGARUH KOMPENSASI FINANSIAL DAN KOMPENSASI NON FINANSIAL TERHADAP KINERJA KARYAWAN PADA PT. SOCFIN INDONESIA MEDAN - Dea Novita Tanjung; Ngatno Sahputra; Umar Hamdan Nasution (Universitas Dharmawangsa, 2022)
The purpose of this study was to determine the effect of financial compensation and non-financial compensation on employee performance at PT. Socfin Medan Indonesia. This type of research is quantitative research, namely research that aims to determine the variable X (Independent) against variable Y (dependent). The population in this study were all permanent employees of PT. Socfin Indonesia Medan, totaling 190 employees from several divisions. The sampling in this study used random sampling with the Slovin technique with an error rate of 10% as many as 63 respondents. The techniques used to collect data in this study were documentation studies, interviews and questionnaires. The analysis used is Multiple Linear Regression analysis, Classical Assumption Test, t test, F test and coefficient of determination. From the results of this study, it was found that the t-test of the X1 variable against Y obtained tcount (2.225) > t table 1.670 with a significant level of 0.030 < 0.50. The t-test of the X2 variable against Y obtained t count 1.680 > t table 1.670 with a significant level of 0.048 <0.05, F test obtained 30.499 > 3.150, the value of 30.499 is greater than 3,150 tcount is greater than t table. The coefficient of determination obtained is 0.504. This means that 50.4% of the variation in employee performance variables (Y) is influenced by the two independent variables, namely financial compensation (X1) and non-financial compensation (X2). So it can be concluded that there is a significant influence on financial compensation. and Non-Financial Compensation on employee performance at PT. Socfin Indonesia Medan.